Gamma Corrected Bright Channel Filtering Based Fast Single Image De-hazing (International Journal of Engineering and Computer Science, 2015)
The proposed research work is based on the concept of visibility enhancement in obtuse weather conditions like dense fog for camera captured images and then the post enhancement process to improve the quality of the data in fog effected images. As the calculation of feature defogging must meet continuous necessity, another technique is proposed, it utilizes the gamma light correction framework of the RGB image frame and joins with light variance model to astutely distinguish foggy scenes in an image. Since the foundations of mechanical work pictures by and large change gradually, median filter is utilized to get frontal affected areas. The transmission of bright channel earlier is redesigned by forefront. At that point every casing is restored straightforwardly as per the more current transmission. The defogging calculation enormously diminishes the running time and hence the processing id also reduced to one third of the base method. It accomplishes the reason for practical application of image defogging. Test results demonstrate that the calculation has a high precision on recognizing foggy scenes.